The Influence of Workload, Non-Physical Work Environment, and Employee Engagement on the Job Satisfaction - Reskha Primaharanti; Siti Sarah (Jurnal Mirai Management, 2023)
The purpose of this research is to examine and analyze the influence of work load, non-physical work environment and Employee Engagement on the job satisfaction at the PT XYZ. This study used quantitative method. A Cluster Random Sampling was used for this study. The analysis unit were the employees of the Production Division at the PT XYZ as many as 75 respondents. The data analysis technique used was multiple linear regression using SPSS version 26. The results of this study indicate that partially workload has a negative and significant effect on the job satisfaction. The non-physical work environment has a significant effect on the job satisfaction. Employee Engagement has a significant effect on the job satisfaction. Simultaneously work load, non-physical work environment, and Employee Engagement has significant influence on job satisfaction of Production Employees’ of PT XYZ. The influence of work load, non-physical work environment, and Employee Engagement is indicated by the Adjusted R Square value of 70,3% and the remaining 29,7% is influenced by other variables that not examined in this study.